2009
DOI: 10.1007/s12104-009-9182-4
|View full text |Cite
|
Sign up to set email alerts
|

1H, 13C and 15N assignments of a camelid nanobody directed against human α-synuclein

Abstract: Nanobodies are single chain antibodies that are uniquely produced in Camelidae, e.g. camels and llamas. They have the desirable features of small sizes (Mw < 14 kDa) and high affinities against antigens (Kd approximately nM), making them ideal as structural probes for biomedically relevant motifs both in vitro and in vivo. We have previously shown that nanobody binding to amyloidogenic human lysozyme variants can effectively inhibit their aggregation, the process that is at the origin of systemic amyloid disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…The affinities of Nbs are comparable or superior to those of conventional Ab derivatives; 15 Nbs with 100 pM affinity constants have been isolated. 35,50 The fast retrieval of high-affinity and target-specific Nbs provides a rich pool for intracellular signaling molecules, protein-protein interactions, and cancer biomarkers. Nbs can be fused with fluorescent proteins to produce chromobodies that may be utilized in single-molecule localization with super-resolution imaging techniques.…”
Section: Therapeutic Applications Safety and Tolerabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The affinities of Nbs are comparable or superior to those of conventional Ab derivatives; 15 Nbs with 100 pM affinity constants have been isolated. 35,50 The fast retrieval of high-affinity and target-specific Nbs provides a rich pool for intracellular signaling molecules, protein-protein interactions, and cancer biomarkers. Nbs can be fused with fluorescent proteins to produce chromobodies that may be utilized in single-molecule localization with super-resolution imaging techniques.…”
Section: Therapeutic Applications Safety and Tolerabilitymentioning
confidence: 99%
“…23 The hydrophilic content and the CDR3 loop folding confer thermal tolerance, aggregation resistance, and conformational stability at extreme pH values and in the presence of chaotropic agents. 28 Melting points are in the range of 67°C-78°C, 50 with thermal unfolding often shown to be fully reversible; functional activity can be retained up to 90°C. 21 The ruggedness of Nbs is suitable for harsh-condition engineering, 27,44 tumor targeting, 15 and surfactant-based pharmaceutical formulations.…”
Section: Therapeutic Applications Safety and Tolerabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Vuchelen et al [78] reported a camelid VHH nanobody, NbSyn2, which bound to the C-terminal of α-Syn. This nanobody, obtained by immunization followed by phage display, has a high affinity for monomeric α-Syn (Kd1 0 nM).…”
Section: Pd and α-Syn As A Targetmentioning
confidence: 99%